Manufacturing Stocks and Forward-Looking Expectations in the UK. - Hall, S; Henry, S; Wren-Lewis, S (1986)
This paper derives a model of the stocks plan based on optimal behavior by the firm when facing adjustment costs with forward-looking expectations formation. Estimates of the model are reported for manufacturing, using three alternative expectations mechanisms for determining expected sales: time series; published forecasts (derived from National Institute published forecasts); and rational expectations. The latter uses a submodel dependent on weakly exogenous variables. Single equation and whole model comparisons are made of the stocks equation estimated with forward expectations versus a traditional backward-looking model. These favor the forward-looking model.